SCHOOL HEADS' EXPERIENCES IN MANAGING PARENTAL INVOLVEMENT IN ZIMBABWEAN RURAL PRIMARY SCHOOLS - Rameck Mazambara; Mmalefikane Sylvia Sepeng (Social Sciences and Education Research Review)
This study aimed at exploring experiences of school heads in managing parental involvement in primary schools in Bikita District of Zimbabwe to establish the main challenges in involving parents in schools management. Parental involvement in Zimbabwe schools had not yet fully rooted from a colonial history of exclusion when disturbances in the economy affected schools management negatively. Economic disturbances resulted in serious irregular schooling when teachers went on prolonged industrial actions, resulting in very little learning in schools and general lack of development in schools for years. These challenges increased parental indifference, mistrust and hostility. A qualitative approach of case study design was used in this study. Ten school heads were purposefully sampled from best 20 performing schools in the 2020 Grade 7 national examination in the district. Those school heads were interviewed to establish their challenges and responses. The study found that irregular schooling and poor learner performance as well as lack of development in schools have caused parents to loose trust in school heads and teachers. In response, school heads became more inclusive and consultative in their leadership approaches to bring back parental trust. The government has to fund schools better and pay teachers better to bring back normalcy in schools. School Management Teams have to develop, follow and create space for parental involvement programmes in their schools for parents to play their roles effectively.